Intensive, Short-Term Presenting With a Science Outreach Program Enhances Positive Science Attitudes and Interest in Lifelong Learning About Science - Sripaoraya, Nantida; Spronken-Smith, Rachel; Longnecker, Nancy (Frontiers in Education, 2022)
This study investigated whether attitudes towards science and interest in lifelong learning about science were impacted by intensive, short-term participation as a science outreach presenter. Participants included students from high schools or universities who volunteered to assist as presenters over one week when Science Caravan – the most extensive science outreach program in Thailand, run by the National Science Museum (NSM) – visited their locality. This study employed mixed methods over two phases. Phase one involved three questionnaires. Two questionnaires were administered to current presenters (N = 690), pre-presenting (before training) and post-presenting at 12 locations of the Science Caravan tour in 2017-18. A third questionnaire collected data from previous, alumni presenters (N = 726). Phase two involved interviews with current presenters (n = 19) and alumni presenters (n = 19). While presenters already possessed positive attitudes towards science, the brief but intensive experience of being a Science Caravan presenter enhanced science attitudes in four scales – with more positive attitudes about Self-concept in science, Value of science to society and Future participation in science, and decreased Anxiety about science presenting. Participation was that presenting had a greater impact of reducing anxiety for female presenters than for males. Science Caravan provided a valuable experience for presenters, which led to the development of more positive attitudes towards science including students' interest in science-related education, and increased interest in lifelong learning activities regarding science. The increase in interest in lifelong learning activities was related to students’ attitudes and self-efficacy in science. This study provides evidence that a short-term, intensive experience of science outreach can lead to increases in positive attitudes towards science and lifelong learning.